Evaluation of the effect of supplementing fermented milk with quinoa flour on probiotic activity - Casarotti, Sabrina N. [UNESP]; Carneiro, Bruno M. [UNESP]; Penna, Ana Lucia B. [UNESP] (Elsevier B.V., 2014)
In this work, we investigated the effect of supplementing fermented milk with quinoa flour as an option to increase probiotic activity during fermented milk production and storage. Fermented milk products were produced with increasing concentrations of quinoa flour (0, 1, 2, or 3 g/100 g) and submitted to the following analyses at 1, 14, and 28 d of refrigerated storage: post-acidification, bacterial viability, resistance of probiotics to simulated gastrointestinal (GI) conditions, and adhesion of probiotics to Caco-2 cells in vitro. The kinetics of acidification were measured during the fermentation process. The time to reach maximum acidification rate, time to reach pH 5.0, and time to reach pH 4.6 (end of fermentation) were similar for all treatments. Adding quinoa flour had no effect on fermentation time; however, it did contribute to postacidification of the fermented milk during storage. Quinoa flour did not affect counts of Bifido bacterium animalis ssp. lactis BB12 or Lactobacillus acidophilus La-5 during storage, it did not protect the probiotic strains during simulated GI transit, and it did not have a positive effect on the adhesion of probiotic bacteria to Caco-2 cells in vitro. Additionally, the adhesion of strains to Caco-2 cells decreased during refrigerated storage of fermented milk. Although the addition of up to 3% quinoa flour had a neutral effect on probiotic activity, its incorporation to fermented milk can be recommended because it is an ingredient with high nutritive value, which may increase the appeal of the product to consumers.
Keywords: functional food; fermented dairy product; probiotic; gastrointestinal resistance; Caco-2 adhesion